TYPOMORPHISM AND GENESIS OF STRONTIOPYROCHLORE AND BARIOPYROCHLORE - Lapin A.V. (My University, 1987)
The problem of the origin of bariopyrochlore and strontiopyrochlore in weathered carbonatite mantle must be solved by special methods, including systematic study of pyrochlore compositions in the supergene alteration zone and in underlying primary rocks, as well as detailed mineralogic examination of pyrochlore, analysis of its zoning and phase inhomogeneity and, finally, investigation of component distributions within inhomogeneous grains. Such work was done on samples from one Siberian carbonatite complex. The study of lateritic weathered carbonatite mantle has provided convincing proof that its strontiopyrochlore and bariopyrochlore are products of the supergene alteration of normal primary pyrochlore by cation-exchange reactions. The most important of these proofs are discussed.